Lenalidomide in Pretreated Mantle Cell Lymphoma Patients: An Italian Observational Multicenter Retrospective Study in Daily Clinical Practice (the Lenamant Study). (19th April 2018) - Stefoni, Vittorio; Pellegrini, Cinzia; Broccoli, Alessandro; Baldini, Luca; Tani, Monica; Cencini, Emanuele; Figuera, Amalia; Ansuinelli, Michela; Bernocco, Elisa; Cantonetti, Maria; Cox, Maria Christina; Ballerini, Filippo; et al.
Abstract: Background: Mantle cell lymphoma (MCL) has the worst prognosis of B‐cell subtypes owing to its aggressive clinical disease course and incurability with standard chemo‐immunotherapy. Options for relapsed MCL are limited, although several single agents have been studied. Lenalidomide is available in Italy for patients with MCL based on a local disposition of the Italian Drug Agency. Subjects, Materials, and Methods: An observational retrospective study was conducted in 24 Italian hematology centers with the aim to improve information on effectiveness and safety of lenalidomide use in real practice. Results: Seventy patients received lenalidomide for 21/28 days with a median of eight cycles. At the end of therapy, there were 22 complete responses (31.4%), 11 partial responses, 6 stable diseases, and 31 progressions, with an overall response rate of 47.1%. Eighteen patients (22.9%) received lenalidomide in combination with either dexamethasone ( n = 13) or rituximab ( n = 5). Median overall survival (OS) was reached at 33 months and median disease‐free survival (DFS) at 20 months: 14/22 patients are in continuous complete response with a median of 26 months. Patients who received lenalidomide alone were compared with patients who received lenalidomide in combination: OS and DFS did not differ. Progression‐free survivals are significantly different: at 56 months, 36% in the combination group versus 13% in patients who received lenalidomide alone. Toxicities were manageable, even if 17 of them led to an early drug discontinuation. Conclusion: Lenalidomide therapy for relapsed MCL patients is effective and tolerable even in a real‐life context. Implication for Practice: Several factors influence treatment choice in relapsed/refractory mantle cell lymphoma (rrMCL), and the therapeutic scenario is continuously evolving. In fact, rrMCL became the first lymphoma for which four novel agents have been approved: temsirolimus, lenalidomide, ibrutinib, and bortezomib. The rrMCL therapeutic algorithm is not so well established because data in the everyday clinical practice are still poor. Lenalidomide for rrMCL patients is effective and tolerable even in a real‐life context. Abstract : An observational retrospective study was conducted in 24 Italian hematologic centers with the aim of improving information on the effectiveness and safety of lenalidomide when given in everyday clinical practice. Results are reported here.